La literatura infantil y su incidencia en el desarrollo de la creatividad de estudiantes de 4 a 5 años del Centro Educativo Básica General “Carlos Finlay”, Quevedo. 2022 - Merchan Moreira, José Andrés (2022)
When children's literature is associated with the development of creativity in education, it is often found that the main problem is that this approach has been understood as giving students the freedom to learn in their own way. This is an erroneous conception of children's literature since this approach, what it actually states is that there is an interaction between the teacher and the students, an interaction between the teacher so that the students have knowledge of what he can contribute to their knowledge, that the contents are reviewed to achieve meaningful learning. At the “Carlos Finlay” General Basic Educational Center, Quevedo. 2022, a teaching methodology of the teacher is manifested, applying the subject of literature in a normal way and without interaction towards the students, this project seeks to analyze the influence of creativity in the teaching and learning processes in the students of 4 to 5 years of the aforementioned institution. Types of research with an applicative purpose and an explanatory scope were used, in addition to the fact that it is proposed to elaborate a contribution to cultivate the interest of the students for their integral formation with the activities that have the purpose of integrating the teachers and students in the construction of knowledge. and in this way carry out meaningful learning collectively.